Strategi Pemasaran Kopi Si Talbak Di Kecamatan Pollung Kabupaten Humbang Hasundutan Provinsi Sumatera Utara (Studi Kasus PT Penabur Benih Indonesia) - Rista Pintaria Br Sinaga; Defidelwina; Sischa Febriani Yamesa Away (SUNGKAI, 2024)
Marketing of Si Talbak coffee at PT Penabur Benih Indonesia is still not optimal so there are still products that have not been sold. The type of research carried out was quantitative descriptive. Data collection was carried out by observation, interviews and documentation. The aim of this research is to analyze the marketing strategy for Si Talbak coffee at PT Penabur Benih Indonesia and determine strategic priorities that are suitable for the company. In order to obtain the required strategy, use the IFAS matrix, EFAS matrix, IE matrix, SWOT matrix and QSPM matrix. Strategic priorities obtained from the results of the analysis include carrying out product development, updating flavor innovations, highlighting product superiority, maximizing the application of production technology and information to increase productivity and business promotion, market expansion, contracting with farmers, and increasing the stability and professionalism of source work. human power. Â  Â